Investigation of steel flow stress and plasticity at high temperatures - Golja, Marijan (Kovine zlitine tehnologije, 1999)
The steel flow stress and plasticity by elevated temperatures are investigate. The results of hot torsion tests in the temperature range from 1073 K to 1473 K (800°C-1200°C) on different steels are presented and discussed.
Keywords: jekla; meja tečenja; plastičnost; temperaturna odvisnost